ANALISIS PEMBELAJARAN DARING DI SEKOLAH DASAR PADA MASA PANDEMI COVID 19 - Zuhrotul muna; Joko Sulianto; A.Y Soegeng (Jurusan Tarbiyah dan Pendidikan, 2022)
Since the Covid-19 pandemic we have known courageous learning, this has happened as a phenomenon due to the Covid-19 pandemic. Where all activities from home, as well as in the field of education, especially at the elementary school level. Elementary school students where they still like to learn while playing and understand better with the information provided by the teacher through concrete objects or direct activities, have now turned completely virtual. This requires the creativity and innovation that teachers need to create fun learning. The purpose of this study was to analyze the learning experienced during distance learning or distance learning, including the media used during bold learning as well as the strengths and obstacles found during the learning process. This research uses a literature review method with a qualitative approach. The data analysis technique used is the Miles and Huberman model, through four stages of analysis. The first data collection (data collection), the second data reduction (data reduction), the third data display (data presentation), and the fourth is drawing conclusions/verification (drawing conclusions and levers). The results of the study show that students who dare to take advantage of using applications that are often chosen, one of which is WhatsApp, because of the convenience and practicality of social media. Keywords: Online Learning; elementary school; WhatsApp